KEKERASAN DALAM RUMAH TANGGA PERSPEKTIF KITAB UQUD AL-LUJJAINYN DAN HAK ASASI MANUSIA - Erfania Zuhriah (El-QUDWAH, 2007)
Domestic violence that has been a polemic is one of the problems that have to be viewed from many aspects: law, culture, and religion in order to get the alternative solution. Since this problem can harm both the wife and the husband. Research Problem in this study is: Why should be illustrated such pattern of relationship between husband and wife within Uqud Al-Lujjayn? How is point of view of human right to domestic violence? Based on these research problem, this study is conducted to find out the answer  Why should be illustrated such pattern of relationship between husband and wife within Uqud Al-Lujjayn; and find out how  point of view of human right to domestic violence is. This research is a normative law research or library research. The data of this research are taken from literature that explains or analyzes about the matter that is based on principles, theories, religion norms, law norm related to domestic violence. From the findings, it could be concluded that Uqud Al-Lujjayn fi Huquq al Zaujan as the masterpiece of Syaikh Nawawi, tt Al Battany or al Jawi is one of fiqh1 books that discuss about household matter especially about wife and husband right. This book is a product of Moslem scholar that changes into a product of Islamic law that creates obligation and right for every member of a family according to fiqh version. As one of the product of Moslem scholar’s interpretation and judgment (ijtihad), Uqud Al-Lujjayn does not apart from subjectivity and ideology of Syaikh Nawawi himself.Keyword: Domestic Violence, Human Rights, Uqud Al-Lujjainyn